2013
DOI: 10.1038/nprot.2013.082
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic mixer designed for performing single-molecule kinetics with confocal detection on timescales from milliseconds to minutes

Abstract: Microfluidic mixing in combination with single-molecule spectroscopy allows the investigation of complex biomolecular processes under non-equilibrium conditions. Here we present a protocol for building, installing and operating microfluidic mixing devices optimized for this purpose. The mixer is fabricated by replica molding with polydimethylsiloxane (PDMS), which allows the production of large numbers of devices at a low cost using a single microfabricated silicon mold. The design is based on hydrodynamic foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 80 publications
(105 citation statements)
references
References 54 publications
1
104
0
Order By: Relevance
“…This process results in an approximately exponential decay in the fluorescence correlation curve, where the corresponding , it is thus necessary to quantify both c q and τ q , ideally under conditions where the protein is completely unfolded, so that f u does not affect the amplitude. Here, we used a microfluidic mixing device that allows us to dilute the protein rapidly from fully denaturing (3 M GdmCl) to native conditions (0.3 M GdmCl) or intermediate GdmCl concentrations with millisecond dead time (51), enabling the observation of unfolded-state dynamics for all conditions before the protein folds. Measurements of the FRETlabeled protein in the microfluidic device confirmed that the protein was predominantly unfolded at times less than 5 ms after dilution of the denaturant (SI Appendix and SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This process results in an approximately exponential decay in the fluorescence correlation curve, where the corresponding , it is thus necessary to quantify both c q and τ q , ideally under conditions where the protein is completely unfolded, so that f u does not affect the amplitude. Here, we used a microfluidic mixing device that allows us to dilute the protein rapidly from fully denaturing (3 M GdmCl) to native conditions (0.3 M GdmCl) or intermediate GdmCl concentrations with millisecond dead time (51), enabling the observation of unfolded-state dynamics for all conditions before the protein folds. Measurements of the FRETlabeled protein in the microfluidic device confirmed that the protein was predominantly unfolded at times less than 5 ms after dilution of the denaturant (SI Appendix and SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Dual-focus fluorescence correlation spectroscopy measurements were performed at 22°C on a MicroTime 200 confocal microscope equipped with a differential interference contrast prism as described previously (29). For rapid mixing experiments, microfluidic mixers were fabricated and used as described previously (23). Molecular dynamics simulations of DnaKrhodanese complexes were performed with CafeMol 2.0 (43) based on a Cα representation of the rhodanese chain and a structure-based model of DnaK bound to the binding sites predicted by LIMBO (44).…”
Section: Methodsmentioning
confidence: 99%
“…1C, colored histograms). As a reference state in the absence of chaperones and denaturant, we thus transiently populate denatured rhodanese in a microfluidic mixing device by rapid dilution of guanidinium chloride (GdmCl) (19,(21)(22)(23). In contrast to native rhodanese, all denatured rhodanese variants exhibit a similar and high transfer efficiency of ∼0.8, which suggests the presence of a compact denatured state ensemble under these conditions (24).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The measurements were recorded on a modified MicroTime 200 instrument (PicoQuant) using a setup for pulsed interleaved excitation (PIE (26)) with two excitation pulses for the donor dye alternating with a single acceptor pulse. The initial phase of protomer formation was measured in a microfluidic mixer (27), and the later phase as well as the pore formation kinetics was constructed from repeated manual mixing measurements (Table 1). All measurements were done at a nominal concentration of labeled ClyACys of 300 pM in PBS with 0.001% (w/v) Tween 20 and 0.1% (w/v) DDM at 22°C.…”
Section: Methodsmentioning
confidence: 99%